Lower trapezius tendon transfer for massive irreparable rotator cuff tears improves outcomes in patients with high grade fatty infiltration of teres minor - Eva Gusnowski, MD, FRCSC; Eric Wagner, MD; Sheila McRae, PhD; Hayden Cooke, MD; Anthony Karzon, MD; Michael Gottschalk, MD; Peter MacDonald, MD, FRCSC; Jarret Woodmass, MD, FRCSC (JSES International)
Background: This study compares postoperative outcomes of lower trapezius tendon transfers (LTTTs) in massive irreparable rotator cuff (RC) tears based on the degree of teres minor (TM) fatty infiltration. Methods: In this prospective longitudinal observational study, patients with massive RC tears undergoing arthroscopic-assisted LTTT by two surgeons were screened. TM fatty infiltration on preoperative magnetic resonance imaging was graded using the Goutallier classification. Two groups were created as follows: group A included grades 0 and 1 (no or little fatty infiltration), and group B included grades 2 to 4 (moderate-to-severe fatty infiltration). Participants completed the Single Assessment Numeric Evaluation (SANE) score preoperatively, and 12- and/or 24 months postoperatively along with a clinical assessment. Independent t-tests compared groups, and paired t-tests compared pre-vs. postoperative results. Significance was defined as P < .05. Results: There were 47 patients in group A and 19 in group B. No group differences were found in preoperative SANE score, forward elevation or active external rotation (ER). Both groups showed significant postoperative improvements in SANE score with no differences between the groups. An ER lag sign was observed in 18/47 patients (38.3%) in group A and 11/19 patients (57.9%) in group B (P = .177). Preoperative ER strength was significantly different in group A (2.9 kg) vs. group B (0.7 kg; P = .001), but postoperative ER strength was similar (P = .931). Conclusion: LTTT is a suitable salvage procedure regardless of the degree of TM fatty infiltration and should be considered an alterative procedure to latissimus dorsi tendon transfer in patients with high-grade TM fatty infiltration.